PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN PENGENDALIAN PERSEDIAAN BARANG MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN MIN-MAX BERBASIS WEB (STUDI KASUS : APOTEK SAHABAT QITA) - Prabawa, Gde Gung; Darmawiguna, I Gede Mahendra; Wirawan, I Made Agus (Jurnal Nasional Pendidikan Teknik Informatika (JANAPATI), 2018)
Inventory control is very important because the shortage or excess inventory is a factor that triggers an increase in cost. Excess inventory will make the cost incurred to be greater and risk of damage or expiration, whereas if a small inventory of goods will be at risk to unmet demand that will decrease the cost of income. This research is developed in line with the problems often faced at the Sahabat Qita pharmacy. Seeing this developed a decision support system inventory control by using methods EOQ (Economix Order Quantity) and Min-Max. The uniqueness of this EOQ method is to determine the amount of economical supply ordering with quick settlement, while the Min-max method can control the inventory of goods maximum and minimum as well as time to place an order. From the results of testing the system capable to help consider and determine the policy amount of ordering, maximum inventory and minimum inventory so as to optimize costs.